Faktor-Faktor Psikologis sebagai Determinan Kepatuhan Pajak: Studi Eksplorasi pada Wajib Pajak - Elis Anisah Fitriah; Zulrizka Iskandar; Wilis Srisayekti; Zainal Abidin (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This study aimed to explore the cognition of taxpayers related to their experience in reporting income tax and understand what the influencing factors on the willingness to pay taxes. Interpretative phenomenology design was applied through semi-structured interviews to four taxpayers as participants. Data was analyzed by developing of textures and structural descriptions. The results showed that psychological factors that considered by participant in their tax behavior including knowledge about the system and tax regulation as well as information on the use of tax returns; perceived service and trust in tax authority. Further research is needed to understand the dynamics of psychological variables in influencing tax behavior with cooperative perspective instead of compliance to avoid punishment.